Use of Nanocarriers Containing Antitrypanosomal Drugs for the Treatment of Chagas Disease - Diogo de Freitas Paiva; Ana Paula dos Santos Matos; Denise de Abreu Garófalo; Tatielle do Nascimento; Mariana Sato de Souza de Bustamante Monteiro; Ralph Santos-Oliveira; Eduardo Ricci-Junior (Pharmaceuticals, 2023)
Chagas disease, caused by the Trypanosoma cruzi parasitic protozoan, is a neglected tropical disease (NTD) of significant incidence in Latin America. Transmission to humans and other mammals is mainly via the vector insect from the Reduviidae family, popularly known as the kissing bug. There are other transmission means, such as through congenital transmission, blood transfusions, organ transplantations, and the consumption of contaminated food. For more than 50 years, the disease has been treated with benznidazole and nifurtimox, which are only effective during the acute phase of the disease. In addition to their low efficacy in the chronic phase, they cause many adverse effects and are somewhat selective. The use of nanocarriers has received significant attention due to their ability to encapsulate and release therapeutic agents in a controlled manner. Generally, their diameter ranges from 100 to 300 nanometers. The objective of this scoping review was to perform a search of the literature for the use of nanocarriers as an alternative for improving the treatment of Chagas disease and to suggest future research. Bibliographic searches were carried out in the Web of Science and PubMed scientific databases from January 2012 to May 2023, using the “Chagas disease and Trypanosoma cruzi and nanoparticles” keywords, seeking to gather the largest number of articles, which were evaluated using the inclusion and exclusion criteria. After analyzing the papers, the results showed that nanocarriers offer physiological stability and safety for the transport and controlled release of drugs. They can increase solubility and selectivity against the parasite. The in vitro assays showed that the trypanocidal activity of the drug was not impaired after encapsulation. In the in vivo assays, parasitemia reduction and high survival and cure rates in animals were obtained during both phases of the disease using lower doses when compared to the standard treatment. The scoping review showed that nanocarriers are a promising alternative for the treatment of Chagas disease.